Timing childhoods: An alternative reading of children's development through philosophy of time, temporality, place and space. (December 2016) - Tesar, Marek
This article argues that the denial of development can be a productive space and a liberating time for children in the current outcomes-driven times. The author offers an alternative reading of childhood, considering children's development differently through various philosophical theorizations of events, which emerge through utilizing philosophy and theory as a method. This approach allows a merging of analyses of childhood, philosophical concepts of time and temporality, place, space and popular culture, in order to outline how the development of a child may be resisted through the notion of 'time and temporality'. The idea of working with the temporality of 'timing childhoods' can mimic the notion of a ticking clock. Positioned against the background of the story of Peter Pan, this article challenges established ways of thinking of/about childhood and development, arguing that they perpetuate inequalities, homogenize children and essentialize childhoods. It thinks divergently with theories and philosophies about how childhoods are conceptualized and dissected, distinguished and 'timed'. The denial of development could be a very power-disrupting, and therefore liberating and exhilarating, experience for children and their childhoods, as the different theoretical and philosophical frameworks analysed in this article point out, through time, temporality and space.